Geografske dileme - Vrišer, Igor (Geografski vestnik, 2007)
The author assesses the strengths and weaknesses of the third successive group of Slovenian geographers, active between 1945 and 1990, which he himself belongs to. Their achievements include increases in the number and staffing of geographical research institutes and departments, a greater volume of published research, following global developmental trends in geography, inclusion in international geographical circles, and the completion and publication of basic Slovenian synthetic works on geography.
Keywords: geografija; geography; slovenski geografi; Slovenia; Slovenija